Active-learning Strategies for Legal Topics and Substance Abuse in a Pharmacy Curriculum - Steinhardt, Sarah J; Clark, John E; Kelly, William N; Hill, Angela M (American journal of pharmaceutical education, 2017)
To implement active-learning strategies to engage students in learning, applying, and teaching legal and substance abuse topics. Medication Safety course student groups created films on a National Patient Safety Goal (NPSG) using a movie genre and presented them in film festival format. Pharmacogenomics course student groups taught ethical, legal, and social implications (ELSI) topics through presentation of short stories about comic book characters with genetic mutations. Students in the Drugs of Abuse course composed and performed dances depicting the mechanism of action of a drug in an in-class rave dance format. Course evaluations revealed student engagement with subject material and enjoyment of the creative applications, critical thinking, and collaborative aspects of the activities. Students performed well on examination questions and graded assignments. These active-learning strategies facilitated students' abilities to learn, apply, and teach material in medication safety, pharmacogenomics, and substance abuse courses.